Harmonic detection in distribution systems using wavelet transform and support vector machine - S. Tuntisak (2018)
This paper presents a method to detect the order of harmonic in distribution power system using wavelet transform and support vector machine. First, a wavelet transform has been used for extract feature of power quality disturbance from the distribution system signal. Then support vector machine is applied to classify the distortion contribution and order of harmonic from different sub-band coefficients. By techniques of support vector machine, power disturbance types and order of harmonic can be detected. From simulation results, the accuracy achieved is satisfied. ©2007 IEEE.